1940
DOI: 10.1029/tr021i002p00628
|View full text |Cite
|
Sign up to set email alerts
|

A distinction between bed‐load and suspended load in natural streams

Abstract: Problems pertaining to the transportation of sediment by flowing water have been extensively studied by engineers and scientists during the last few years. Most of the various experiments have been concerned with either bed‐load or suspended load, but seldom have they been studied simultaneously. When bed‐load and suspended load occur simultaneously in a flume or stream a distinct difference in their mechanical composition is often observed. A curve fitted to the plotted data from a mechanical analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

1963
1963
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 2 publications
2
45
0
1
Order By: Relevance
“…The analysis of the wash load has proved difficult in that, unlike the bed and suspended loads, the concentration and total transport rate of the wash load do not always relate to the river-flow parameters (t~, u., discharge or flow power) (Einstein et a/., 1940: Colby, 1963: Guy, 1964. Instead, (7) the concentration depends more upon the geology of the river's drainage basin and upon the climate.…”
Section: Wash-load Transportmentioning
confidence: 99%
“…The analysis of the wash load has proved difficult in that, unlike the bed and suspended loads, the concentration and total transport rate of the wash load do not always relate to the river-flow parameters (t~, u., discharge or flow power) (Einstein et a/., 1940: Colby, 1963: Guy, 1964. Instead, (7) the concentration depends more upon the geology of the river's drainage basin and upon the climate.…”
Section: Wash-load Transportmentioning
confidence: 99%
“…bed load, suspended load, wash load) and a bed function and wash load, which are independent of riverbed variation. This is a fundamental concept in the derivation of all theoretical sediment transport formulae (Einstein et al, 1940;Einstein, 1950;Bagnold, 1966Bagnold, , 1973Bagnold, , 1977Ashida and Michiue, 1972;Ackers and White, 1973;Kiat et al, 2008;Konrad, 2009;Rajaee, 2011;Xue et al, 2012;Haddadchi et al, 2013). Bed material load comprises both bed load and suspended load, which consist of grain sizes represented in the bed, and moves downstream either as bed load or as suspended material that is constantly exchanging with the bed.…”
Section: Simulation Approachmentioning
confidence: 98%
“…A total number of 329 data records are used in the study including monthly average rainfalls [mm], air temperature [8C], discharge [m 3 /s] and suspended-sediment [tons/year]. The first 165 of these data records are used to determine the weights of the models (training stage) and the remaining 164 are exploited for testing the models.…”
Section: Establishment Of the Modelsmentioning
confidence: 99%
“…Since 1940, there have been a few studies including that of Einstein et al [3] for the Enoree River and Nordin and Dempster [4] for the Rio Grande, which express the view that rainfall and initial flow have a major effect on sediment load changes. Data obtained from seven rivers in the United States of America Atlantic region were analyzed, and it was found that the sediment loads are due to flow discharge, peak flow, amount of rainfall and its frequency [5].…”
Section: Introductionmentioning
confidence: 98%